Modelling continuance intention of citizens in government Facebook page: A complementary PLS approach - Valaei, Naser *; Baroto, Bambang (Elsevier, 2017)
The main purpose of this paper is to examine the continuance intention (CI) of citizens in following government Facebook page. Applying theories of expectation-confirmation, and information system success on a sample of 362 students in Malaysia, and using Partial Least Squares-Structural Equation Modelling (PLS-SEM), the study finds that CI and satisfaction of government Facebook page is contingent upon information quality (IQ) of the Facebook page per se. IQ is found as a second order construct of five first order factors: reliability, completeness, relevancy, timeliness, and understandability. Satisfaction of government Facebook page is also found as a partial mediator to the relationship between IQ and CI of following government Facebook page. In addition, applying PLS multi-group analysis, the results show that different government Facebook pages moderate the relationships between IQ and satisfaction of government Facebook page, IQ and CI of following government Facebook page as well as satisfaction of government Facebook page and CI of following government Facebook page.